INCREASING CONFIDENCE FOR THE BLIND WITH BRAILE DARE OR TRUTH CARD GAMES IN MUHAMMADIYAH SCHOOL OF DIFABLE JOMBANG - Rena Harnadia; Sovia Harvianti Eguweleira; Iklil Fairuza Diniah Rumantyo; Cahyani Ariniil Himmah; Mochamad Misbachussudur; Choirinnisa Meilia Ayu Putri; Mohammad Ali Hanafi; Elvira Sari Dewi (Caring : Jurnal Pengabdian Masyarakat, 2021)
Blind people tend to feel insecure when socializing with other people because of their limitations. Braille Dare or Truth (B-DoT) Card is an innovation of playing cards for the visually impaired designed to increase self-confidence. The purpose of this activity is to find out the benefits of the B-DoT Card game in increasing the confidence of the blind at SLB Muhammadiyah Jombang. Beginning with making a B-DoT Card designed using Adobe Illustrator, printed, and added braille manually using a reglet and stylus. After the card was finished, it was continued by visiting SLB Muhammadiyah Jombang to interact directly with blind people in August 2021. Two blind people were found who were willing to participate in this activity. Blind people are taught, trained, and assisted in playing B-DoT Card games while observing the self-confidence shown by the blind. The observations included being more confident attitude towards self-ability, optimism is a positive view of hope in playing the game, objective is a view of the problem in accordance with the reality that occurs, rational is thinking that is accepted by sense and in accordance with reality. Before the game was played, the blind people showed an attitude lack of confidence. In contrast, after the game, the blind people showed an attitude of confidence. The B-DoT Card game can be recommended as an effort to increase self-confidence for blind people at SLB Muhammadiyah Jombang.